Current knowledge of the family Pompilidae (Hymenoptera: Vespoidea) in Mexico: diversity and geographical distribution - Vanoye-Eligio, Maximiliano; Gómez-Camal, María Del Carmen; Martín-Canché, Blanca Del Rosario; Rosas-Mejía, Madai; Horta-Vega, Jorge V.; Vanoye-Eligio, Venancio (Zootaxa, 2021)
The family Pompilidae is a little-known insect group in Mexico, which comprises insects known as spider-hunting wasps. This study aimed to review and update the occurrence of pompilids in Mexico and provide information on their geographical distribution. A total of 305 species and 46 genera were compiled, of which 131 species and 11 genera were added to the Pompilidae species list in Mexico. Moreover, we provided data on the geographical distribution of 216 Pompilidae species and highlighted 126 species as registered only from this country, which accounted for 41 % of the total species. The nearctic portion in Mexico is the most studied area, with 203 species, whereas only 96 species are listed from the neotropical region of the country. Four subfamilies were represented: Pompilinae with 161 species, Pepsinae with 128 species, Ceropalinae with ten species, and Notocyphinae with six species. Anoplius was the most species-rich genus with 41 species, and Sericopompilus neotropicalis was the most widely distributed species. The analysis suggests a high diversity of the family Pompilidae and underlines the need to further explore southern areas of Mexico.